Mental Schemas Hamper Memory Storage of Goal-Irrelevant Information - Sweegers, C. C. G.; Coleman, G. A.; van Poppel, E. A. M.; Cox, R.; Talamini, L. M. (Frontiers in Human Neuroscience, 2015)
Mental schemas exert top-down control on information processing; for instance by facilitating the storage of schema-related information. However, given capacity-limits and competition in neural network processing, schemas may additionally exert their effects by suppressing information with low momentary relevance. In particular, when existing schemas suffice to guide goal-directed behavior, this may actually reduce encoding of the redundant sensory input, in favor of gaining efficiency in task performance. The present experiment set out to test this schema-induced shallow encoding hypothesis. Our approach involved a memory task in which faces had to be coupled to homes. For half of the faces the responses could be guided by a pre-learned schema, for the other half of the faces such a schema was not available. Memory storage was compared between schema-congruent and schema-incongruent items. To characterize putative schema effects, memory was assessed both with regard to visual details and contextual aspects of each item. The depth of encoding was also assessed through an objective neural measure: the parietal old/new ERP effect. This ERP effect, observed between 500-800 ms post stimulus onset, is thought to reflect the extent of recollection: the retrieval of a vivid memory, including various contextual details from the learning episode. We found that schema-congruency induced substantial impairments in item memory and even larger ones in context memory. Furthermore, the parietal old/new ERP effect indicated higher recollection for the schema-incongruent than the schema-congruent memories. The combined findings indicate that, when goals can be achieved using existing schemas, this can hinder the in-depth processing of novel input, impairing the formation of perceptually detailed and contextually rich memory traces. Taking into account both current and previous findings, we suggest that schemas can both positively and negatively bias the processing of sensory input. An important determinant in this matter is likely related to momentary goals, such that mental schemas facilitate memory processing of goal-relevant input, but suppress processing of goal-irrelevant information.